Sedum aizoon L.: a review of its history, traditional uses, nutritional value, botany, phytochemistry, pharmacology, toxicology, and quality control - Wang, Bai-Ling; Ge, Zhen-Kai; Qiu, Jing-Ran; Luan, Si-Qi; Hao, Xin-Cai; Zhao, Yong-Heng (Frontiers in Pharmacology, 2024)
and Mexico, Sedum aizoon L. ( S. aizoon) is used as an edible plant. Up to now, over 234 metabolites including phenolic acids, flavonoids, triterpenes, phytosterols, and alkaloids, among others, have been identified. In addition to its antioxidant, anti-inflammatory, anti-fatigue, antimicrobial, anti-cancer, and hemostatic activity, S. aizoon is used for the treatment of cardiovascular disease. This paper provides an overview of the history, botany, nutritional value, traditional use, phytochemistry, pharmacology, toxicology and quality control of S. aizoon.